2017
DOI: 10.4081/itjm.2017.719
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the antioxidant drug U-74389G on urea levels during ischemia reperfusion injury in rats

Abstract: This experimental study examined the effect of the antioxidant drug U-74389G, on a rat model and particularly in a renal ischemia-reperfusion protocol. The effects of that molecule were studied biochemically using blood mean urea levels. Forty rats of mean weight 231.875 g were used in the study. Urea levels were measured at 60 min of reperfusion (groups A and C) and at 120 min of reperfusion (groups B and D). The drug U-74389G was administered only in groups C and D. U-74389G administration significantly decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…These membrane-associated antioxidants are particularly effective in preventing permeability changes in brain microvascular endothelial cell monolayers (2). The same authors of that study found the influence of U-74389G, as depicted in Table 1, on some seric variable levels in related IR injury experiments at the same endpoints with the present experiment after clamp removal in rats (3,4). 3693/12-11-2010 and 14/10-1-2012 decisions.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…These membrane-associated antioxidants are particularly effective in preventing permeability changes in brain microvascular endothelial cell monolayers (2). The same authors of that study found the influence of U-74389G, as depicted in Table 1, on some seric variable levels in related IR injury experiments at the same endpoints with the present experiment after clamp removal in rats (3,4). 3693/12-11-2010 and 14/10-1-2012 decisions.…”
Section: Introductionsupporting
confidence: 72%
“…The experiment started with animals subjected to pre-narcosis followed by general anesthesia, as described in detail in related references (3,4). Their electrocardiogram, acidometry, and oxygen supply were continuously provided.…”
Section: Introductionmentioning
confidence: 99%
“…The unique available study investigating the hypophosphoremic effect of U-74389G was the preliminary one 1 . Although the most famous activities of neuroprotection and membrane-stabilization properties, it accumulates in the cell membrane, protecting vascular endothelium from peroxidative damage but hardly penetrates the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The Vet licenses under 3693/12-11-2010 & 14/10-1-2012 numbers, the granting company and the experiment location are mentioned in preliminary references [1,2]. The human animal care of Albino female Wistar rats, the 7 days pre-experimental ad libitum diet, the non-stop intraexperimental anesthesiologic techniques, the acidometry, the electrocardiogram, the oxygen supply and post-experimental euthanasia are also described in preliminary references.…”
Section: Animal Preparationmentioning
confidence: 99%
“…7 days pre-experimental normal housing included ad libitum diet in laboratory. Prenarcosis of animals proceeded of continuous intra-experimental general anesthesia [3][4][5][6], oxygen supply, electrocardiogram and acidometry. Post-experimental euthanasia did not permitted awakening and preservation of the animals.…”
Section: Animal Preparationmentioning
confidence: 99%